2013
DOI: 10.1111/iju.12161
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of preoperative hematological disorders and a risk stratification model in bladder cancer patients treated with radical cystectomy

Abstract: Abbreviations & Acronyms ASA = American Society of Anesthesiologists BCa = bladder cancer BMI = body mass index CCI = Charlson Comorbidity Index CI = confidential interval CRP = C-reactive protein DSS = disease-specific survival ECOG = Eastern Cooperative Oncology Group eGFR = estimated glomerular filtration rate HB = hemoglobin HR = hazard ratio LDH = lactate dehydrogenase LNM = lymph node metastasis LVI = lympho-vascular invasion NA = not available PS = performance status PSM = positive surgical margin RC = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…Previous work has found an association between clinical outcomes after RC and PS, namely Karnofsky PS [5] and ECOG PS [16]. The preoperative Hb concentration is reported to be associated with disease-specific survival of patients treated with RC [17,18]. Consistent with previous data, we found that ECOG PS and preoperative Hb level were associated with OS after RC for the entire cohort (Tables 3, 5).…”
Section: Discussionsupporting
confidence: 90%
“…Previous work has found an association between clinical outcomes after RC and PS, namely Karnofsky PS [5] and ECOG PS [16]. The preoperative Hb concentration is reported to be associated with disease-specific survival of patients treated with RC [17,18]. Consistent with previous data, we found that ECOG PS and preoperative Hb level were associated with OS after RC for the entire cohort (Tables 3, 5).…”
Section: Discussionsupporting
confidence: 90%
“…Another model incorporated preoperative hemoglobin (<10.5 g/dL), elevated CRP (>5.0 mg/L), pathologic T stage (≥pT3a), positive surgical margin, and nodal disease, all of which were independently prognostic of cancerspecific survival in bladder cancer, into a risk stratification model. The 4-year cancer-specific survival for low risk, intermediate risk, and high risk patients was 77.7%, 23.6%, and 7.4%, respectively (Sejima et al, 2014). When various pairs out of the three separate risk groups were compared, differences were noted to be significant.…”
Section: Bladder Cancermentioning
confidence: 95%
“…Sejima et al . also reported that CRP elevation above 0.5 mg/dL was associated with poor prognosis in the patients with bladder cancer treated with radical cystectomy . LN‐positive patients with low preoperative CRP levels might derive survival benefits from AC, after RNU, and this option should be offered to them.…”
Section: Discussionmentioning
confidence: 98%